Utilization of Jamun seed powder in composite cake formulation - Marufa, Mushtari Akter; Das, Pabitra Chandra; Iqbal, Abdullah (Journal of the Bangladesh Agricultural University, 2019)
The study is concerned with the evaluation of the nutritional and functional properties of Jamun seed powder (JSP) extracted from fresh Jamun and to develop cakes by incorporating JSP with wheat flour (WF). The chemical analysis showed that JSP had 6.30% moisture, 6.24% protein, 2.19% ash, 1.18% fat, 84.09% carbohydrate and 371.94 Kcal energy/100 g of powder whereas WF contained 12.90% moisture, 11.00% protein, 1.35% ash, 1.50% fat, 73.01% total carbohydrate and 349.54 Kcal energy/100 g of powder. Four cake samples were prepared by using different proportion combination of WF and JSP such as A (100% WF), B (90% WF and 10% JSP), C (80% WF and 20% JSP) and D (70% WF and 30% JSP). The nutritional components of four cake samples gave the range of moisture 16.92-25.56%, protein 6.34-8.56%, ash 1.50-2.60%, fat 16.01-22.42% and total carbohydrate 41.96-58.13%. Weight (g) of processed cakes were increased whereas other physical attributes such as volume, height, specific volume were decreased due to supplementation of JSP. The increased level of JSP powder substitution changed the crust color of cakes from light brown to blackish and also changed the crumb color from brownish to reddish. Sensory evaluation indicated that the sample B (10% JSP and 90% WF) was the most acceptable by the panelists than those of other cakes. Above all, the study gave an indication that Jamun seed powder can be used as a good replacement of wheat flour in production of cakes which can help to get higher energy, mineral and carbohydrate. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 599–605, 2019